Development of an Interactive Guest Reception Website Application to Improve Administrative Services at Universitas Sindang Kasih Majalengka Using the RAD Method: Pengembangan Aplikasi Website Penerimaan Tamu Interaktif untuk Meningkatkan Pelayanan Administrasi di Universitas Sindang Kasih Majalengka dengan Metode RAD - Irfan, Moch Taufik; Maturidi, Ade Johar (CV. Media Publikasi Profesional, 2025)
Universitas Sindang Kasih Majalengka (USKM) is a higher education institution committed to improving the quality of administrative services, including guest data management, which was previously performed manually and lacked efficiency. This study aims to develop an interactive guest reception website application using the Bootstrap framework to support the digitalization of guest registration and reporting processes. The research employed the Rapid Application Development (RAD) method, which consists of the stages of requirements planning, design workshop, implementation, testing, and deployment, enabling a fast and structured development process. System requirements data were collected through observation, interviews, and literature studies, then implemented into a responsive and user-friendly interface design. The testing results show that the application increased the efficiency of guest registration processes by up to 80% compared to the manual system and received positive feedback from users regarding accessibility and service speed. The application also features data management, automatic report generation, and user validation to ensure information security. In conclusion, the interactive guest reception system successfully provides faster, more accurate, and more professional services within USK Majalengka. The contribution of this research lies in applying the RAD method to develop an efficient, adaptive, and web-based administrative service information system that supports the digital transformation of higher education institutions.